The effect of glycine, N-acetylcysteine, and L-theanine on Klotho, sirtuin 1, and interleukin-1β in the blood plasma of domestic cats - Protopopov Vladimir A.; Sekunov Alexey V.; Toropova Tatiana V.; Burganova Dilyara N.; Bryndina Irina G. (BIO Web of Conferences)
The study’s relevance lies in the growing interest in influencing age-related processes in pets by adjusting their diets, including the use of varying amino acid contents and ratios. The main aim was to evaluate the impact of feeding domestic cats amino acid supplements containing glycine, N-acetylcysteine (NAC), and L-theanine (L-The) on the levels of Klotho protein, interleukin-1-beta (IL-1β), and sirtuin-1 (SIRT1) in blood plasma. Twenty-one adult cats were divided into three groups, each receiving food with one of these supplements: glycine (Gly), NAC, or L- The. After six weeks, the cats’ general condition and body weight were recorded, and plasma levels of SIRT1, Klotho, and IL-1β were measured by Western blot. The results were compared to baseline (Wilcoxon test). NAC significantly lowered IL-1β levels and showed a trend toward higher SIRT1. L-The increase Klotho levels. In the Gly group, no statistically significant changes were observed, although there was a trend toward elevated SIRT1 and IL-1β. These findings suggest certain beneficial effects of these amino acid-enriched diets on markers linked to aging. However, given the short trial duration, these data remain preliminary. They require further in-depth studies with extended intake periods, careful dose adjustments, and comprehensive combination evaluations in future research.